Analisis ANALISIS EFISIENSI RUMAH SAKIT BERDASARKAN GRAFIK BARBER JOHNSON TAHUN 2017 DI RUMAH SAKIT ISLAM GONDANGLEGI - miftachul ulum (ITKM WIDYA CIPTA HUSADA, 2020)
Efficiency is one of the parameters / performance indicators that theoretically underlies the entire performance of an organization in this case is the hospital service. One of the services provided in the hospital is hospitalization. Assessment of hospital efficiency, can use Barber Johnson chart. In this graph there is an area called the efficiency area. Gondanglegi Islamic Hospital in 2017 still does not meet the predefined Barber Johnson chart standards and in 2017 decreased bed usage levels. The purpose of this study is to analyze the efficiency of Gondanglegi Islamic Hospital service in 2017 through the Barber Barber approach. The research method is using descriptive research with quantitative approach. The results explain that the meeting point at Barber Johnson Graph is outside the efficiency area. Factors that cause services in Gondanglegi Islamic Hospital is not efficient is the utilization of SIMRS less than the maximum, the number of patients is still a little because of the promotion of the management is still minimal. Keywords: Efficiency analysis, hospital, barber charts johnson